The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1753-0407.12914
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of high mobility group box 1 (HMGB1) attenuates podocyte apoptosis and epithelial‐mesenchymal transition by regulating autophagy flux

Abstract: Background Podocyte injury, characterized by podocyte hypertrophy, apoptosis, and epithelial‐mesenchymal transition (EMT), is the major causative factor of diabetic nephropathy (DN). Autophagy dysfunction is regarded as the major risk factor for podocyte injury including EMT and apoptosis. High mobility group box 1 (HMGB1) is involved in the progression of DN through the induction of autophagy. However, the underlying mechanism remains unknown. Methods Plasma HMGB1 concentrations were determined in DN patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
(72 reference statements)
0
24
0
Order By: Relevance
“…HMGB1 is a damage-related molecular pattern that can be actively or passively released from various cells under different conditions and plays a key role in the pathogenesis of inflammation and angiogenesis-dependent diseases (33). Additionally, HMGB1 is involved in the development of T2DM by inducing autophagy (34), and HMGB1 deletion can inhibit podocyte EMT by inhibiting TGF-β/smad1 signaling (35).…”
Section: Mir-92d-3p Suppressed the Progression Of Dn Disease By Inhibiting The Activationmentioning
confidence: 99%
“…HMGB1 is a damage-related molecular pattern that can be actively or passively released from various cells under different conditions and plays a key role in the pathogenesis of inflammation and angiogenesis-dependent diseases (33). Additionally, HMGB1 is involved in the development of T2DM by inducing autophagy (34), and HMGB1 deletion can inhibit podocyte EMT by inhibiting TGF-β/smad1 signaling (35).…”
Section: Mir-92d-3p Suppressed the Progression Of Dn Disease By Inhibiting The Activationmentioning
confidence: 99%
“…In this study, we proposed that the molecular mechanism behind the effect of CLEC14A on the regulation of inflammatory response is most likely related to its ability to inhibit HMGB1 signaling. Emerging evidence has indicated that HMGB1 is involved in podocyte injury 25,26 . HMGB1 is a DNA‐binding nuclear protein, released actively following cytokine stimulation and passively during cell injury and death.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Jin and colleagues [53] studied the effect of STIM1 on autophagy and epithelial-mesenchymal transition (EMT) in podocytes in diabetic nephropathy. They found that, in podocytes cultured in the serum of diabetic nephrotic rats, autophagy decreased, whereas EMT increased and that both changes reverse after silencing STIM1.…”
Section: Discussionmentioning
confidence: 99%